mathlib documentation

tactic.ring_exp

ring_exp tactic

A tactic for solving equations in commutative (semi)rings, where the exponents can also contain variables.

More precisely, expressions of the following form are supported:

The motivating example is proving 2 * 2^n * b = b * 2^(n+1), something that the ring tactic cannot do, but ring_exp can.

Implementation notes

The basic approach to prove equalities is to normalise both sides and check for equality. The normalisation is guided by building a value in the type ex at the meta level, together with a proof (at the base level) that the original value is equal to the normalised version. The normalised version and normalisation proofs are also stored in the ex type.

The outline of the file:

There are some details we glossed over which make the plan more complicated:

Caveats and future work

Subtraction cancels out identical terms, but division does not. That is: a - a = 0 := by ring_exp solves the goal, but a / a := 1 by ring_exp doesn't. Note that 0 / 0 is generally defined to be 0, so division cancelling out is not true in general.

Multiplication of powers can be simplified a little bit further: 2 ^ n * 2 ^ n = 4 ^ n := by ring_exp could be implemented in a similar way that 2 * a + 2 * a = 4 * a := by ring_exp already works. This feature wasn't needed yet, so it's not implemented yet.

Tags

ring, semiring, exponent, power

meta structure tactic.ring_exp.atom  :
Type

The atom structure is used to represent atomic expressions: those which ring_exp cannot parse any further.

For instance, a + (a % b) has a and (a % b) as atoms. The ring_exp_eq tactic does not normalize the subexpressions in atoms, but ring_exp does if ring_exp_eq was not sufficient.

Atoms in fact represent equivalence classes of expressions, modulo definitional equality. The field index : ℕ should be a unique number for each class, while value : expr contains a representative of this class. The function resolve_atom determines the appropriate atom for a given expression.

The eq operation on atoms works modulo definitional equality, ignoring their values. The invariants on atom ensure indices are unique per value. Thus, eq indicates equality as long as the atoms come from the same context.

We order atoms on the order of appearance in the main expression.

expression section

In this section, we define the ex type and its basic operations.

First, we introduce the supporting types coeff, ex_type and ex_info. For understanding the code, it's easier to check out ex itself first, then refer back to the supporting types.

The arithmetic operations on ex need additional definitions, so they are defined in a later section.

structure tactic.ring_exp.coeff  :
Type

Coefficients in the expression are stored in a wrapper structure, allowing for easier modification of the data structures. The modifications might be caching of the result of expr.of_rat, or using a different meta representation of numerals.

inductive tactic.ring_exp.ex_type  :
Type

The values in ex_type are used as parameters to ex to control the expression's structure.

meta structure tactic.ring_exp.ex_info  :
Type

Each ex stores information for its normalization proof.

The orig expression is the expression that was passed to eval.

The pretty expression is the normalised form that the ex represents. (I didn't call this something like norm, because there are already too many things called norm in mathematics!)

The field proof contains an optional proof term of type %%orig = %%pretty. The value none for the proof indicates that everything reduces to reflexivity. (Which saves space in quite a lot of cases.)

meta inductive tactic.ring_exp.ex  :

The ex type is an abstract representation of an expression with +, * and ^. Those operators are mapped to the sum, prod and exp constructors respectively.

The zero constructor is the base case for ex sum, e.g. 1 + 2 is represented by (something along the lines of) sum 1 (sum 2 zero).

The coeff constructor is the base case for ex prod, and is used for numerals. The code maintains the invariant that the coefficient is never 0.

The var constructor is the base case for ex exp, and is used for atoms.

The sum_b constructor allows for addition in the base of an exponentiation; it serves a similar purpose as the parentheses in (a + b)^c. The code maintains the invariant that the argument to sum_b is not zero or sum _ zero.

All of the constructors contain an ex_info field, used to carry around (arguments to) proof terms.

While the ex_type parameter enforces some simplification invariants, the following ones must be manually maintained at the risk of insufficient power:

  • the argument to coeff must be nonzero (to ensure 0 = 0 * 1)
  • the argument to sum_b must be of the form sum a (sum b bs) (to ensure (a + 0)^n = a^n)
  • normalisation proofs of subexpressions must be refl ps.pretty
  • if we replace sum with cons and zero with nil, the resulting list is sorted according to the lt relation defined further down; similarly for prod and coeff (to ensure a + b = b + a).

The first two invariants could be encoded in a subtype of ex, but aren't (yet) to spare some implementation burden. The other invariants cannot be encoded because we need the tactic monad to check them. (For example, the correct equality check of expr is is_def_eq : exprexprtactic unit.)

Return the proof information associated to the ex.

Return the original, non-normalized version of this ex.

Note that arguments to another ex are always "pre-normalized": their orig and pretty are equal, and their proof is reflexivity.

Return the normalized version of this ex.

Return the normalisation proof of the given expression. If the proof is refl, we give none instead, which helps to control the size of proof terms. To get an actual term, use ex.proof_term, or use mk_proof with the correct set of arguments.

Update the orig and proof fields of the ex_info. Intended for use in ex.set_info.

Update the ex_info of the given expression.

We use this to combine intermediate normalisation proofs. Since pretty only depends on the subexpressions, which do not change, we do not set pretty.

Equality test for expressions.

Since equivalence of atoms is not the same as equality, we cannot make a true (=) operator for ex either.

The ordering on expressions.

As for ex.eq, this is a linear order only in one context.

operations section

This section defines the operations (on ex) that use tactics. They live in the ring_exp_m monad, which adds a cache and a list of encountered atoms to the tactic monad.

Throughout this section, we will be constructing proof terms. The lemmas used in the construction are all defined over a commutative semiring α.

meta structure tactic.ring_exp.eval_info  :
Type

Stores the information needed in the eval function and its dependencies, so they can (re)construct expressions.

The eval_info structure stores this information for one type, and the context combines the two types, one for bases and one for exponents.

meta structure tactic.ring_exp.context  :
Type

The context contains the full set of information needed for the eval function.

This structure has two copies of eval_info: one is for the base (typically some semiring α) and another for the exponent (always ). When evaluating an exponent, we put info_e in info_b.

meta def tactic.ring_exp.ring_exp_m  :
Type → Type

The ring_exp_m monad is used instead of tactic to store the context.

meta def tactic.ring_exp.lift {α : Type} :

Lift an operation in the tactic monad to the ring_exp_m monad.

This operation will not access the cache.

Change the context of the given computation, so that expressions are evaluated in the exponent ring, instead of the base ring.

Specialized version of mk_app where the first two arguments are {α} [some_class α]. Should be faster because it can use the cached instances.

Specialized version of mk_app where the first two arguments are {α} [comm_semiring α]. Should be faster because it can use the cached instances.

Specialized version of mk_app ``has_add.add. Should be faster because it can use the cached instances.

Specialized version of mk_app ``has_mul.mul. Should be faster because it can use the cached instances.

Specialized version of mk_app ``has_pow.pow. Should be faster because it can use the cached instances.

Construct a normalization proof term or return the cached one.

Construct a normalization proof term or return the cached one.

If all ex_info have trivial proofs, return a trivial proof. Otherwise, construct all proof terms.

Useful in applications where trivial proofs combine to another trivial proof, most importantly to pass to mk_proof_or_refl.

Use the proof terms as arguments to the given lemma. If the lemma could reduce to reflexivity, consider using mk_proof_or_refl.

Use the proof terms as arguments to the given lemma. Often, we construct a proof term using congruence where reflexivity suffices. To solve this, the following function tries to get away with reflexivity.

A shortcut for adding the original terms of two expressions.

A shortcut for multiplying the original terms of two expressions.

A shortcut for exponentiating the original terms of two expressions.

theorem tactic.ring_exp.sum_congr {α : Type u} [comm_semiring α] {p p' ps ps' : α} :
p = p'ps = ps'p + ps = p' + ps'

Congruence lemma for constructing ex.sum.

theorem tactic.ring_exp.prod_congr {α : Type u} [comm_semiring α] {p p' ps ps' : α} :
p = p'ps = ps'p * ps = p' * ps'

Congruence lemma for constructing ex.prod.

theorem tactic.ring_exp.exp_congr {α : Type u} [comm_semiring α] {p p' : α} {ps ps' : } :
p = p'ps = ps'p ^ ps = p' ^ ps'

Congruence lemma for constructing ex.exp.

Constructs ex.zero with the correct arguments.

Constructs ex.coeff with the correct arguments.

There are more efficient constructors for specific numerals: if x = 0, you should use ex_zero; if x = 1, use ex_one.

Constructs ex.coeff 1 with the correct arguments. This is a special case for optimization purposes.

theorem tactic.ring_exp.base_to_exp_pf {α : Type u} [comm_semiring α] {p p' : α} :
p = p'p = p' ^ 1

theorem tactic.ring_exp.exp_to_prod_pf {α : Type u} [comm_semiring α] {p p' : α} :
p = p'p = p' * 1

theorem tactic.ring_exp.prod_to_sum_pf {α : Type u} [comm_semiring α] {p p' : α} :
p = p'p = p' + 0

theorem tactic.ring_exp.atom_to_sum_pf {α : Type u} [comm_semiring α] (p : α) :
p = (p ^ 1) * 1 + 0

A more efficient conversion from atom to ex sum.

The result should be the same as ex_var p >>= base_to_exp >>= exp_to_prod >>= prod_to_sum, except we need to calculate less intermediate steps.

Compute the sum of two coefficients. Note that the result might not be a valid expression: if p = -q, then the result should be ex.zero : ex sum instead. The caller must detect when this happens!

The returned value is of the form ex.coeff _ (p + q), with the proof of expr.of_rat p + expr.of_rat q = expr.of_rat (p + q).

theorem tactic.ring_exp.mul_coeff_pf_one_mul {α : Type u} [comm_semiring α] (q : α) :
1 * q = q

theorem tactic.ring_exp.mul_coeff_pf_mul_one {α : Type u} [comm_semiring α] (p : α) :
p * 1 = p

Compute the product of two coefficients.

The returned value is of the form ex.coeff _ (p * q), with the proof of expr.of_rat p * expr.of_rat q = expr.of_rat (p * q).

meta inductive tactic.ring_exp.overlap  :
Type

Represents the way in which two products are equal except coefficient.

This type is used in the function add_overlap. In order to deal with equations of the form a * 2 + a = 3 * a, the add function will add up overlapping products, turning a * 2 + a into a * 3. We need to distinguish a * 2 + a from a * 2 + b in order to do this, and the overlap type carries the information on how it overlaps.

The case none corresponds to non-overlapping products, e.g. a * 2 + b; the case nonzero to overlapping products adding to non-zero, e.g. a * 2 + a (the ex prod field will then look like a * 3 with a proof that a * 2 + a = a * 3); the case zero to overlapping products adding to zero, e.g. a * 2 + a * -2. We distinguish those two cases because in the second, the whole product reduces to 0.

A potential extension to the tactic would also do this for the base of exponents, e.g. to show 2^n * 2^n = 4^n.

theorem tactic.ring_exp.add_overlap_pf {α : Type u} [comm_semiring α] {ps qs pq : α} (p : α) :
ps + qs = pqp * ps + p * qs = p * pq

theorem tactic.ring_exp.add_overlap_pf_zero {α : Type u} [comm_semiring α] {ps qs : α} (p : α) :
ps + qs = 0p * ps + p * qs = 0

Given arguments ps, qs of the form ps' * x and ps' * y respectively return ps + qs = ps' * (x + y) (with x and y arbitrary coefficients). For other arguments, return overlap.none.

theorem tactic.ring_exp.add_pf_z_sum {α : Type u} [comm_semiring α] {ps qs qs' : α} :
ps = 0qs = qs'ps + qs = qs'

theorem tactic.ring_exp.add_pf_sum_z {α : Type u} [comm_semiring α] {ps ps' qs : α} :
ps = ps'qs = 0ps + qs = ps'

theorem tactic.ring_exp.add_pf_sum_overlap {α : Type u} [comm_semiring α] {pps p ps qqs q qs pq pqs : α} :
pps = p + psqqs = q + qsp + q = pqps + qs = pqspps + qqs = pq + pqs

theorem tactic.ring_exp.add_pf_sum_overlap_zero {α : Type u} [comm_semiring α] {pps p ps qqs q qs pqs : α} :
pps = p + psqqs = q + qsp + q = 0ps + qs = pqspps + qqs = pqs

theorem tactic.ring_exp.add_pf_sum_lt {α : Type u} [comm_semiring α] {pps p ps qqs pqs : α} :
pps = p + psps + qqs = pqspps + qqs = p + pqs

theorem tactic.ring_exp.add_pf_sum_gt {α : Type u} [comm_semiring α] {pps qqs q qs pqs : α} :
qqs = q + qspps + qs = pqspps + qqs = q + pqs

Add two expressions.

  • 0 + qs = 0
  • ps + 0 = 0
  • ps * x + ps * y = ps * (x + y) (for x, y coefficients; uses add_overlap)
  • (p + ps) + (q + qs) = p + (ps + (q + qs)) (if p.lt q)
  • (p + ps) + (q + qs) = q + ((p + ps) + qs) (if not p.lt q)
theorem tactic.ring_exp.mul_pf_c_c {α : Type u} [comm_semiring α] {ps ps' qs qs' pq : α} :
ps = ps'qs = qs'ps' * qs' = pqps * qs = pq

theorem tactic.ring_exp.mul_pf_c_prod {α : Type u} [comm_semiring α] {ps qqs q qs pqs : α} :
qqs = q * qsps * qs = pqsps * qqs = q * pqs

theorem tactic.ring_exp.mul_pf_prod_c {α : Type u} [comm_semiring α] {pps p ps qs pqs : α} :
pps = p * psps * qs = pqspps * qs = p * pqs

theorem tactic.ring_exp.mul_pp_pf_overlap {α : Type u} [comm_semiring α] {pps p_b ps qqs qs psqs : α} {p_e q_e : } :
pps = (p_b ^ p_e) * psqqs = (p_b ^ q_e) * qs(p_b ^ (p_e + q_e)) * ps * qs = psqspps * qqs = psqs

theorem tactic.ring_exp.mul_pp_pf_prod_lt {α : Type u} [comm_semiring α] {pps p ps qqs pqs : α} :
pps = p * psps * qqs = pqspps * qqs = p * pqs

theorem tactic.ring_exp.mul_pp_pf_prod_gt {α : Type u} [comm_semiring α] {pps qqs q qs pqs : α} :
qqs = q * qspps * qs = pqspps * qqs = q * pqs

Multiply two expressions.

  • x * y = (x * y) (for x, y coefficients)
  • x * (q * qs) = q * (qs * x) (for x coefficient)
  • (p * ps) * y = p * (ps * y) (for y coefficient)
  • (p_b^p_e * ps) * (p_b^q_e * qs) = p_b^(p_e + q_e) * (ps * qs) (if p_e and q_e are identical except coefficient)
  • (p * ps) * (q * qs) = p * (ps * (q * qs)) (if p.lt q)
  • (p * ps) * (q * qs) = q * ((p * ps) * qs) (if not p.lt q)
theorem tactic.ring_exp.mul_p_pf_zero {α : Type u} [comm_semiring α] {ps qs : α} :
ps = 0ps * qs = 0

theorem tactic.ring_exp.mul_p_pf_sum {α : Type u} [comm_semiring α] {pps p ps qs ppsqs : α} :
pps = p + psp * qs + ps * qs = ppsqspps * qs = ppsqs

theorem tactic.ring_exp.mul_pf_zero {α : Type u} [comm_semiring α] {ps qs : α} :
qs = 0ps * qs = 0

theorem tactic.ring_exp.mul_pf_sum {α : Type u} [comm_semiring α] {ps qqs q qs psqqs : α} :
qqs = q + qsps * q + ps * qs = psqqsps * qqs = psqqs

theorem tactic.ring_exp.pow_e_pf_exp {α : Type u} [comm_semiring α] {pps p : α} {ps qs psqs : } :
pps = p ^ psps * qs = psqspps ^ qs = p ^ psqs

Compute the exponentiation of two coefficients.

The returned value is of the form ex.coeff _ (p ^ q), with the proof of expr.of_rat p ^ expr.of_rat q = expr.of_rat (p ^ q).

theorem tactic.ring_exp.pow_pp_pf_one {α : Type u} [comm_semiring α] {ps : α} {qs : } :
ps = 1ps ^ qs = 1

theorem tactic.ring_exp.pow_pf_c_c {α : Type u} [comm_semiring α] {ps ps' pq : α} {qs qs' : } :
ps = ps'qs = qs'ps' ^ qs' = pqps ^ qs = pq

theorem tactic.ring_exp.pow_pp_pf_c {α : Type u} [comm_semiring α] {ps ps' pqs : α} {qs qs' : } :
ps = ps'qs = qs'ps' ^ qs' = pqsps ^ qs = pqs * 1

theorem tactic.ring_exp.pow_pp_pf_prod {α : Type u} [comm_semiring α] {pps p ps pqs psqs : α} {qs : } :
pps = p * psp ^ qs = pqsps ^ qs = psqspps ^ qs = pqs * psqs

Exponentiate two expressions.

  • 1 ^ qs = 1
  • x ^ qs = x ^ qs (for x coefficient)
  • (p * ps) ^ qs = p ^ qs + ps ^ qs
theorem tactic.ring_exp.pow_p_pf_one {α : Type u} [comm_semiring α] {ps ps' : α} {qs : } :
ps = ps'qs = 1ps ^ qs = ps'

theorem tactic.ring_exp.pow_p_pf_zero {α : Type u} [comm_semiring α] {ps : α} {qs qs' : } :
ps = 0qs = qs'.succps ^ qs = 0

theorem tactic.ring_exp.pow_p_pf_succ {α : Type u} [comm_semiring α] {ps pqqs : α} {qs qs' : } :
qs = qs'.succps * ps ^ qs' = pqqsps ^ qs = pqqs

theorem tactic.ring_exp.pow_p_pf_singleton {α : Type u} [comm_semiring α] {pps p pqs : α} {qs : } :
pps = p + 0p ^ qs = pqspps ^ qs = pqs

theorem tactic.ring_exp.pow_p_pf_cons {α : Type u} [comm_semiring α] {ps ps' : α} {qs qs' : } :
ps = ps'qs = qs'ps ^ qs = ps' ^ qs'

Exponentiate two expressions.

  • ps ^ 1 = ps
  • 0 ^ qs = 0 (note that this is handled after ps ^ 0 = 1)
  • (p + 0) ^ qs = p ^ qs
  • ps ^ (qs + 1) = ps * ps ^ qs (note that this is handled after p + 0 ^ qs = p ^ qs)
  • ps ^ qs = ps ^ qs (otherwise)
theorem tactic.ring_exp.pow_pf_zero {α : Type u} [comm_semiring α] {ps : α} {qs : } :
qs = 0ps ^ qs = 1

theorem tactic.ring_exp.pow_pf_sum {α : Type u} [comm_semiring α] {ps psqqs : α} {qqs q qs : } :
qqs = q + qs(ps ^ q) * ps ^ qs = psqqsps ^ qqs = psqqs

theorem tactic.ring_exp.simple_pf_sum_zero {α : Type u} [comm_semiring α] {p p' : α} :
p = p'p + 0 = p'

theorem tactic.ring_exp.simple_pf_prod_one {α : Type u} [comm_semiring α] {p p' : α} :
p = p'p * 1 = p'

theorem tactic.ring_exp.simple_pf_prod_neg_one {α : Type u_1} [ring α] {p p' : α} :
p = p'p * -1 = -p'

theorem tactic.ring_exp.simple_pf_var_one {α : Type u} [comm_semiring α] (p : α) :
p ^ 1 = p

theorem tactic.ring_exp.simple_pf_exp_one {α : Type u} [comm_semiring α] {p p' : α} :
p = p'p ^ 1 = p'

Give a simpler, more human-readable representation of the normalized expression.

Normalized expressions might have the form a^1 * 1 + 0, since the dummy operations reduce special cases in pattern-matching. Humans prefer to read a instead. This tactic gets rid of the dummy additions, multiplications and exponentiations.

Performs a lookup of the atom a in the list of known atoms, or allocates a new one.

If a is not definitionally equal to any of the list's entries, a new atom is appended to the list and returned. The index of this atom is kept track of in the second inductive argument.

This function is mostly useful in resolve_atom, which updates the state with the new list of atoms.

Convert the expression to an atom: either look up a definitionally equal atom, or allocate it as a new atom.

You probably want to use eval_base if eval doesn't work instead of directly calling resolve_atom, since eval_base can also handle numerals.

Treat the expression atomically: as a coefficient or atom.

Handles cases where eval cannot treat the expression as a known operation because it is just a number or single variable.

theorem tactic.ring_exp.negate_pf {α : Type u_1} [ring α] {ps ps' : α} :
(-1) * ps = ps'-ps = ps'

Negate an expression by multiplying with -1.

Only works if there is a ring instance; otherwise it will fail.

theorem tactic.ring_exp.inverse_pf {α : Type u_1} [division_ring α] {ps ps_u ps_p e' e'' : α} :
ps = ps_ups_u = ps_pps_p⁻¹ = e'e' = e''ps⁻¹ = e''

Invert an expression by simplifying, applying has_inv.inv and treating the result as an atom.

Only works if there is a division_ring instance; otherwise it will fail.

theorem tactic.ring_exp.sub_pf {α : Type u_1} [ring α] {ps qs psqs : α} :
ps + -qs = psqsps - qs = psqs

theorem tactic.ring_exp.div_pf {α : Type u_1} [division_ring α] {ps qs psqs : α} :
ps * qs⁻¹ = psqsps / qs = psqs

wiring section

This section deals with going from expr to ex and back.

The main attraction is eval, which uses add, mul, etc. to calculate an ex from a given expr. Other functions use exes to produce exprs together with a proof, or produce the context to run ring_exp_m from an expr.

Compute a normalized form (of type ex) from an expression (of type expr).

This is the main driver of the ring_exp tactic, calling out to add, mul, pow, etc. to parse the expr.

Run eval on the expression and return the result together with normalization proof.

See also eval_simple if you want something that behaves like norm_num.

Run eval on the expression and simplify the result.

Returns a simplified normalized expression, together with an equality proof.

See also eval_with_proof if you just want to check the equality of two expressions.

Compute the eval_info for a given type α.

Use e to build the context for running mx.

Repeatedly apply eval_simple on (sub)expressions.

Tactic for solving equations of commutative (semi)rings, allowing variables in the exponent. This version of ring_exp fails if the target is not an equality.

The variant ring_exp_eq! will use a more aggressive reducibility setting to determine equality of atoms.

Tactic for evaluating expressions in commutative (semi)rings, allowing for variables in the exponent.

This tactic extends ring: it should solve every goal that ring can solve. Additionally, it knows how to evaluate expressions with complicated exponents (where ring only understands constant exponents). The variants ring_exp! and ring_exp_eq! use a more aggessive reducibility setting to determine equality of atoms.

For example:

example (n : ) (m : ) : 2^(n+1) * m = 2 * 2^n * m := by ring_exp
example (a b : ) (n : ) : (a + b)^(n + 2) = (a^2 + b^2 + a * b + b * a) * (a + b)^n := by ring_exp
example (x y : ) : x + id y = y + id x := by ring_exp!

Normalises expressions in commutative (semi-)rings inside of a conv block using the tactic ring_exp.